Gambaran Karakteristik Konstipasi pada Pasien Stroke - Maria Valentina Sibarani; Rahmi Ulfah; Esi Afrianti (Ners Jurnal Keperawatan, 2019)
Abstract              Constipation is a problem that is often complained of by stroke patients, if not addressed will lead to complications of other diseases. The purpose of this study was to see a description of the characteristics of stroke patients who experience post-treatment constipation. This type of research is descriptive, the number of samples of 54 people taken by simple random sampling. The quosioener used to screen stroke patients is the National Institute of Health Stroke (NIHSS) and the Constipation Scoring System (CSS) for screening patients who experience constipation. The frequency distribution test results are more constipation suffered by women (68.52%), junior high school education (50%), history of IRT work (37.04%), average age of 53 years, stroke duration of 63 months and long time using laxative 23 months. Conclusion:Post-treatment stroke patients often experience constipation caused by disorders of the autonomic nerve and long-term use of laxatives. In addition,constipation in post-treatment stroke patients is influenced by female sex, increasing age, low educational status, IRT employment and duration of stroke. Post-treatment stroke patients to reduce the use of laxatives and replace with more consumption of fiber and fluids and sufficient activity, to minimize the incidence of constipation. Keywords: constipation, stroke, stroke complicationsAbstrakKonstipasi merupakan masalah yang sering dikeluhkan oleh pasien stroke, jika tidak di atasi akan mengakibatkan komplikasi penyakit lainnya. Tujuan dari penelitian ini untuk melihat gambaran karaktersitik pasien stroke yang mengalami konstipasi pasca rawatan. Jenis penelitian ini adalah deskriptif, jumlah sampel 54 orang yang diambil dengan cara simpel random sampling. Kuesioener yang digunakan untuk menskrining pasien stroke adalah National Institute of Health Stroke (NIHSS) dan Kuesioner Constipation Scoring System (CSS) untuk menskrining pasien yang mengalami konstipasi. Hasil uji distribusi frekuensi adalah lebih banyak konstipasi diderita oleh wanita (68,52%), pendidikan sekolah menengah pertama (50%), riwayat pekerjaan IRT (37,04%), rata-rata umur 53 tahun, lama menderita stroke 63 bulan dan lama menggunakan pencahar 23 bulan. Kesimpulan: Pasien stroke pasca rawatan sering mengalami konstipasi diakibatkan oleh gangguan pada saraf otonom  dan  penggunaan pencahar jangka panjang. Selain itu, konstipasi pada pasien stroke pasca rawatan dipengaruhi oleh jenis kelamin wanita, pertambahan usia, status pendidikan yang rendah, pekerjaan IRT serta lama menderita stroke. Pasien stroke pasca rawatan agar mengurangi penggunaan pencahar dan lebih mengganti dengan memperbanyak  konsumsi serat dan cairan serta aktifitas yang cukup, untuk  meminimalkan kejadian konstipasi. Kata kunci:  Konstipasi, komplikasi stroke, stroke